2020
DOI: 10.1007/s40200-020-00635-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis on prevalence and sub-regional distribution of undiagnosed diabetes mellitus among adults in African countries

Abstract: Background Despite the high prevalence of diabetes in Africa, the extent of undiagnosed diabetes in the region is still poorly understood. This systematic review and meta-analysis was designed to determine the pooled prevalence of undiagnosed diabetes mellitus among adults in Africa. Methods We conducted a systematic desk review and electronic web-based search of PubMed, Google Scholar, EMBASE, and the World Health Organization’s Hinari portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
0
14
3
Order By: Relevance
“…Among those with DM, 70% of them were unaware of their DM condition ( 56 ). The findings of the current meta-analysis showed that the prevalence of undiagnosed DM was slightly higher (7%) than other studies from sub-Saharan Africa ( 57 , 58 ). For instance, the prevalence of undiagnosed-DM in one systematic review from 2007 to 2020 among adults in African countries was 3.85% ( 57 ) while another systematic review reported that the prevalence was 5.37% ( 58 ).…”
Section: Discussioncontrasting
confidence: 74%
“…Among those with DM, 70% of them were unaware of their DM condition ( 56 ). The findings of the current meta-analysis showed that the prevalence of undiagnosed DM was slightly higher (7%) than other studies from sub-Saharan Africa ( 57 , 58 ). For instance, the prevalence of undiagnosed-DM in one systematic review from 2007 to 2020 among adults in African countries was 3.85% ( 57 ) while another systematic review reported that the prevalence was 5.37% ( 58 ).…”
Section: Discussioncontrasting
confidence: 74%
“…One study showed mean total weight of salt added to food was nearly double the WHO recommendation, with women adding significantly more salt to food than men [62]. As in other studies in Africa, lack of and limited knowledge is a barrier to effective prevention, diagnosis, and management of NCDs in the region [63][64][65][66][67][68]. Most individuals do not know that they have high BP and others do not take any medication [57].…”
Section: Discussionmentioning
confidence: 99%
“…If COVID-19 is not brought under control and case counts continue increasing, these countries may experience higher levels of hospitalizations and need for intensive care services. This is likely to be worsened by the high prevalence of undiagnosed chronic comorbidities such as diabetes and hypertension (47).…”
Section: Discussionmentioning
confidence: 99%
“…At the time of submission of this review, nine of the included studies (16,17,(35)(36)(37)(38)(39)(40)(41) were published in peer reviewed journals. Of the remaining two studies, one was a letter to the editor (26) and the other a preprint (47). Four studies (16,17,26,42) did not report the mean or median ages of included participant but reported percentages in various age groups.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%